Sarcoidosis presenting as Wallenberg syndrome and panuveitis. (2018) - Oks, Margarita; Li, Albert; Makaryus, Mina; Pomeranz, Howard D.; Sachdeva, Mala; Pullman, James; Schwartz, Dan; Steinberg, Harry
Abstract: Sarcoidosis is a multi-system disease with neurological involvement being one of the more rare manifestations. We report a case of a patient who presented with the lateral medullary syndrome and panuveitis as her initial manifestation of sarcoidosis. The patient's course was further complicated by renal involvement. Lacrimal gland and renal biopsies showed noncaseating granulomas without evidence of infection, establishing the diagnosis. Intracranial vertebral artery involvement was confirmed by brain imaging. Bilateral hilar lymphadenopathy with upper lobe predominant nodules on chest imaging was consistent with asymptomatic pulmonary involvement. Systemic steroid therapy is indicated for treatment of ocular sarcoidosis, with standard stroke management indicated for the treatment of lateral medullary syndrome.